An Experimental Study to Evaluate the Impact of the Programming Paradigm in the Testing Activity - Senger de Souza, Simone de Rocio; Paiva Prado, Marllos; Francine Barbosa, Ellen; Maldonado, José Carlos (CLEI electronic journal, 2012)
Several techniques and criteria are available to help conducting testing activity. The choice for one of them depends on different aspects, such as the time restrictions, ef- fectiveness of the testing criteria or the features of the program under test. In this context, the programming paradigm might influence in the testing activity cost. This paper presents the results of an experimental study to characterize and evaluate the cost and strength of structural and functional testing criteria, comparing object-oriented and procedural programming paradigms. A set of 32 programs from the data structure do- main was considered in this study. The main goals in the execution of this research were: i) to obtain initial results about the investigated questions; ii) to generate artifacts which can be used as basis to define and conduct further experimental studies; iii) to support training and teaching of software testing activity.